1991
DOI: 10.4049/jimmunol.147.1.354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a neutralization epitope on the envelope gp46 antigen of human T cell leukemia virus type I and induction of neutralizing antibody by peptide immunization.

Abstract: We have generated a number of mAb against various epitopes on the external envelope glycoprotein, gp46, of human T cell leukemia virus type I (HTLV-I) from a WKA rat immunized with a recombinant vaccinia virus containing the HTLV-I env gene. Among these mAb, one group of mAb, represented by a mAb designated LAT-27, could neutralize the infectivity of HTLV-I, as determined by a HTLV-I-mediated cell fusion inhibition assay. LAT-27 also interfered with transformation of normal T lymphocytes by HTLV-I in vitro. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To infect target cells with HTLV-1, all cells were plated in 6-well culture plates (1.5 × 10 5 cells per well), and viral stock solution was added to the wells (HTLV-1 p19 antigen = 10 or 20 ng equivalent of virus). In addition, the viral stock solution was preincubated with or without the HTLV-1 envelope-specific neutralizing monoclonal antibody ( 70 ), LAT-27 (10 or 20 µg/mL) for 1 hour at 37°C. To deplete extracellular matrix structures, the viral stock solution was filtrated through a 0.45 or 0.20 µm filter (Sartorius, Göttingen, Germany) before infection.…”
Section: Methodsmentioning
confidence: 99%
“…To infect target cells with HTLV-1, all cells were plated in 6-well culture plates (1.5 × 10 5 cells per well), and viral stock solution was added to the wells (HTLV-1 p19 antigen = 10 or 20 ng equivalent of virus). In addition, the viral stock solution was preincubated with or without the HTLV-1 envelope-specific neutralizing monoclonal antibody ( 70 ), LAT-27 (10 or 20 µg/mL) for 1 hour at 37°C. To deplete extracellular matrix structures, the viral stock solution was filtrated through a 0.45 or 0.20 µm filter (Sartorius, Göttingen, Germany) before infection.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid pSV HTLV-1 env (kindly provided by Dr. R. Sutton, Baylor College of Medicine, Houston, TX, USA) and pCAGHTLV-1 env (obtained from Dr. K. Okuma, Kyushu University, Kukuoka, Japan) both express the HTLV-1 env gene under the SV40 and CMV promoter, respectively [ 33 , 34 ]. Anti-gp46 antibodies used in this study included the rat monoclonal antibody LAT-27 (kindly provided by Dr. Y. Tanaka, University of the Ryukyus, Okinawa, Japan) [ 35 ] and monoclonal antibodies SP2,3/4A (rabbit) and 0.5α (human) [ 36 , 37 ], both of which were provided by the NIH HIV Reagent Program and are known to be neutralizing.…”
Section: Methodsmentioning
confidence: 99%
“…The 293T cells were then transfected with HTLV-1 Env and HTLV-1-or HIV-1-Gag-Venus vectors. The cell surface expression level of HTLV-1 Env in the Gag Venus-positive cell population was analyzed by flow cytometry using an anti-HTLV-1 gp46 mAb, LAT-27 (Figure 2A) [24]. We found that the expression of HTLV-1 Env increased in the presence of HTLV-1 or HIV-1 Gag.…”
Section: Inefficient Incorporation Of Htlv-1 Env Into Vlps Carrying H...mentioning
confidence: 96%
“…The 293T cells were transfected with the HTLV-1 Env expression plasmid (pcDNA-1E-RRE) and either pCRVI/HTLV-1/Gag-Venus or pCRVI/HIV-1/Gag-Venus, as described above. The cells were recovered 24 h post-transfection using a cell dissociation solution (Sigma-Aldrich), stained with the anti-gp46 rat mAb LAT-27 [24]. The cells were then further stained with APC-conjugated anti-rat IgG (Bioligands, San Diego, CA, USA) and fixed with 4% paraformaldehyde for 15 min.…”
Section: Flow Cytometrymentioning
confidence: 99%